From modern pathogenetic insights and molecular understanding to new deescalating therapeutic strategies in gastric MALT-lymphoma - Fischbach, Wolfgang; Eck, Matthias; Rosenwald, Andreas (Zeitschrift für Gastroenterologie, 2024)
Based on new insights into the aetiology and pathogenesis of gastric marginal-zone B-cell lymphoma of MALT (MALT-lymphoma) and its histomorphological and molecular characteristics, important progress in our understanding of the disease and its clinical management has been made during the last decades. A landmark in this development was the identification of Helicobacter pylori as the decisive pathogenetic factor for gastric MALT lymphoma. We, here, give an overview about the history and the current knowledge of the histology, genetics, and molecular characteristics and pathogenesis of gastric MALT lymphoma. We then focus on how these findings have fundamentally changed its clinical management over the last three decades with consequent deescalating therapeutic strategies.
Keywords: gastric MALT lymphoma; Helicobacter pylori; pathogenesis; histology; genetics; clinical management